Schmoller's Grundriss der Nationalokonomie (Quarterly Journal of Economics, 1895)
Journal Article Schmoller's Grundriss der Nationalökonomie Get access The Quarterly Journal of Economics, Volume 9, Issue 3, April 1895, Page 345, https://doi.org/10.1093/qje/9.3.345-a Published: 01 April 1895